2012
DOI: 10.2310/8000.2012.110485
|View full text |Cite
|
Sign up to set email alerts
|

Emergency physician estimates of the probability of acute coronary syndrome in a cohort of patients enrolled in a study of coronary computed tomographic angiography

Abstract: Introduction: Little information exists regarding how accurately emergency physicians (EPs) predict the probability of acute coronary syndrome (ACS). Our objective was to determine if EPs can accurately predict ACS in a prospectively identified cohort of emergency department (ED) patients who met enrolment criteria for a study of coronary computed tomographic angiography (CCTA) and were admitted for a ''rule out ACS'' protocol. Methods: A prospective observational pilot study in an academic medical centre was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Overall, unstructured risk estimates were associated with overestimation of ACE risk. This finding is in line with previous research examining whether clinical gestalt is accurate for ruling out AMI 2–5. Such studies have reported moderate to high sensitivity for ruling out patients, but specificity is very low, typically around 20%–30% 3 5.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, unstructured risk estimates were associated with overestimation of ACE risk. This finding is in line with previous research examining whether clinical gestalt is accurate for ruling out AMI 2–5. Such studies have reported moderate to high sensitivity for ruling out patients, but specificity is very low, typically around 20%–30% 3 5.…”
Section: Discussionsupporting
confidence: 91%
“…Gestalt is an appealing method of risk stratification due to its flexibility and inherent availability 2. Existing studies have shown that physician estimates of risk have moderate to high sensitivity for ruling out ACEs but tend to be conservative and overestimate risk 3–5. Such studies have dichotomised risk estimates into low-risk and high-risk when examining accuracy.…”
Section: Introductionmentioning
confidence: 99%